The Impacts of the Day of the week Effect on The JII Returns and Risks - Rida Rahim; Dery Berlian M (Jurnal Ilmiah Poli Bisnis, 2020)
This study aims to examine the impacts of the day of the week effect on stock returns and measurements of risks in companies listed on the Jakarta Islamic Index (JII) for the June 2018-May 2019 period. The sample consisted of 28 companies. This study found that there is an influence of the day of the week effect on the Jakarta Islamic Index stock returns. It partially showed that the Monday effect had a significant negative effect on the JII stock returns. While the Friday effect had a positive and significant effect on the Jakarta Islamic Index stock returns. In the buy and sell decision-making, investors may firstly consider and look at the trends in the market. In addition, this study revealed that there was no significant difference between the results of the measurement of risk (value-at-risk) with the historical simulation and variance-covariance methods on the JII stock risk for the June 2018-May 2019 period. This was due to differences in sampling techniques, sample selection, and the period of observation. Key words : day of the week effect, Monday effect, Friday effect, return, VaR, Historical Simulation